Reviewing the Development of Hong Kong's School Physical Education through History: 從歷史看香港學校體育的發展 - WONG, Arthur Chi Tak (Asian Journal of Physical Education & Recreation, 1999)
LANGUAGE NOTE | Document text in Chinese; abstract also in English. This paper describes briefly the history of school physical education in Britain and China. Alongside, the author provides bits and pieces of information about Hong Kong's school physical education in an anecdotal manner hoping to fill up partly the lacuna of local history in school physical education. Against this background, problems concerning curriculum development, classroom teaching and teacher training are discussed. 本文先簡述英國及中國的學校體育的歷史背景，再透過筆者在香港從事體育敎育工作多年累積的經驗及所見所聞：拋磚引玉，為香港學校體育空白的歷史填上一筆的同時，藉此提出一些香港學校體育在課程發展及敎學上所遇到的問題，與體育工作者共同探討。